Moral leadership and its relationship to methods of managing organizational conflict among middle school principals in the State of Kuwait from the teachers' point of view - Al- Rasheedi, Ahmed Obied (Journal of Educational and Psychological Sciences, 2021)
This study aimed at revealing moral leadership and its relationship to methods of managing organizational conflict among middle school principals in the State of Kuwait from the teachers' point of view, and the basic Hypothesis of this study is: There is no statistically significant correlation at the significance level (0.05 = α) between the level of moral leadership And methods of managing organizational conflict among middle school principals in the State of Kuwait from the teachers' point of view. The relational descriptive method was followed, and a sample consisting of (411) teachers from middle schools in the Farwaniya area in Kuwait was chosen in an accessible way, and two developed questionnaires were applied to them. They are: the ethical leadership questionnaire, and the methods of managing organizational conflict, and the indications of their validity and reliability were verified. The results of the study found that the level of moral leadership among middle school principals in the State of Kuwait was average from the teachers ’point of view, and came after professional relations in the first rank, while personal characteristics came second and last, and that the method of cooperation in managing organizational conflict among school principals The average level in the State of Kuwait from the teachers ’point of view came first and at an intermediate level, then the negotiation method, then the method of coercion, and finally the method of avoidance. Between the level of moral leadership and the two methods of avoidance and compulsion in managing organizational conflict among school principals, the study came out with a set of recommendations, the most important of which is emphasizing the commitment of school principals to moral leadership, training principals and school principals on methods of managing organizational conflict in their schools, and conducting more studies in primary schools. And secondary.
Keywords: Moral Leadership; Managing Organizational Conflict; Principals; Secondary School; Kuwait